Distribution and ecology of dictyostelids in China. Issue 4 (December 2020) - Liu, Pu; Zhang, Shunhang; Zou, Yue; Li, Zhuang; Stephenson, Steven L.; Li, Yu
Abstract: Dictyostelid cellular slime molds are a ubiquitous component of most soils, where they feed upon bacteria and other microbes and thus play an essential role in the soil ecosystem. Herein we review the available literature on dictyostelid cellular slime molds in China, especially their diversity and ecology. The patterns of distribution for these organisms in relation to the different habitats with which they are associated are analyzed and discussed. In addition, the assemblages of dictyostelids reported from China and the United States were compared. The CC value obtained (0.48) indicates that China and the United States are perhaps less similar than might be expected. Our data point out the need for further studies to characterize more completely the assemblages of dictyostelids associated with particular vegetation types or particular regions throughout the world. Highlights: The diversity and ecology of dictyostelids in China were analyzed. The assemblages of dictyostelds reported from China and the United States are compared and discussed.